The Making of MoRENet - Janz, Robert; Chemane, Lourino (My University, 2015)
Although MoRENet has been defined in 2002 and included in the National ICT Policy Implementation Strategy of Mozambique as one of the priority projects in the area of education, only in in 2005 the pilot phase of this network started covering some institutions in Maputo , and it took until 2014 before MoRENet started to provide national services. The reasons for this long gestation period and how they were dealt with can be lessons for other emerging National Research and Education Networks (NRENs). The discussion of MoRENet initiative started during the formulation of the ICT Policy Implementation Strategy in 2001, and it has been defined as a project with the aim of providing affordable Internet services for the Higher Education and Research sector in Mozambique. The first attempt to build a national network for research and higher education and implement the envisaged services in Mozambique did not take off for various reasons, the most important being that the initiative was not well embedded within the stakeholders and also because there was no sound financial plan. NRENs are often presented as a technical solution to provide affordable Internet services, with the higher education and research sector as sole beneficiary. It is wiser to address society priorities related to the Networked Readiness of the country when trying to prove the case of the NREN. In 2011 the MoRENet initiative got back to the momentum it had in 2005, this time as a joint project of the Ministry of Science and Technology and the Ministry of Education and Culture. At the end of 2012 a financial plan was presented that forecast that, with initial funding from the World Bank, through the Mozambique eGovernment and Communication Infrastructure Project (MEGCIP), MoRENet would be financial sustainable in 2016. Since 2014 MoRENet is providing services and in 2015 has reached national coverage.
Keywords: NREN; MoRENet; Business Model; Research and Education; Connectivity; Internet Services